Pembentukan Karakter Integritas dan Nilai-Nilai Cinta Tanah Air Melalui Sosialisasi Pendidikan Dini Antikorupsi - Anwar, Arman; Adidharma, Arnedi Rizki; Susilo, Adriyanto; Isnaini, Andhini Shafa (AIWADTHU: Jurnal Pengabdian Hukum, 2024)
Introduction: Corruption in Indonesia is increasingly pervasive, prompting the President to declare a war on corruption. Anti-corruption education plays a crucial role in combating this issue. One effective strategy is to engage Gen Z in anti-corruption efforts, leveraging their ability to rapidly disseminate information through online platforms, which can significantly contribute to preventing and eradicating corruption as a form of love for Indonesia's homeland.Purposes of Devotion: To enhance and motivate students to participate in anti-corruption efforts in alignment with the characteristics and strengths of Gen Z. Method of Devotion: The initiative involves in-person sessions with speakers, followed by interactive discussions where participants have the opportunity to ask questions about the role of Gen Z in combating corruption, tailored to their specific characteristics and advantages.Results of the Devotion: Students at SMP Negeri 27 Maluku Tengah gained a deeper understanding of the importance of anti-corruption education in shaping anti-corruption character and became more engaged in anti-corruption efforts. The creativity and innovation of Gen Z students, coupled with their proficiency in communication and information technology, position them as key players in preventing and addressing corruption. Their ability to swiftly spread information via online platforms, such as social media, can be harnessed to advocate for integrity and transparency in government and public institutions. Educational initiatives, empowerment, and support for anti-corruption efforts can further strengthen the positive role of Gen Z in promoting societal integrity and welfare.